Post-exercise cold- and contrasting-water immersion effects on heart rate variability recovery in international handball female players - Ravier, G.; Marcel-Millet, P.; Fostel, C.; Baradat, E. (Journal of Human Kinetics, 2022)
This study aimed to investigate the effect of water immersion (WI) on cardiac parasympathetic reactivation during recovery from handball training sessions in elite female players during a two-week training camp. On the first three days of both weeks, players completed a crossover design with one of three 60-min delayed post-exercise WI protocols or passive rest (PAS). Recovery interventions consisted of a period of 6-min cold-WI (10°C; CWI6) and two contrasting periods cold- and hot-WI (36°C): one session included 3 min cold + 2 min hot + 3 min cold and the other session 5 × 2 min with cold at the very end. Short-term measures of heart rate variability (HRV) were collected before and after handball training sessions, and after WI. Derived parasympathetic HRV indices collected daily showed lower values post-training compared to pre-training values (p < 0.0001, large ES). Individual handball training sessions revealed similar clear depression of the vagal tone throughout the training camp. The comparison between each WI protocol and PAS revealed significant time × condition interaction particularly for CWI6. All parasympathetic indices revealed higher post-recovery values in CWI 6 than PAS (p < 0.001 - p < 0.0001, with large ES ranging from 0.86 to 0.94). Surprisingly, 60-min delayed post-training WI revealed for most of parasympathetic HRV indices higher values than pre-training. This study highlighted that post-exercise parasympathetic disruption was exacerbated in response to handball training, and the 60-min delayed WI recovery interventions improved parasympathetic reactivity. Cardiac vagal tone can be highly improved with CWI6 compared to PAS. For the purpose of HRV modulations, CWI6 is recommended for short-term recovery.